2013
DOI: 10.1044/1059-0889(2013/13-0001)
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Resolution With a Prescriptive Fitting Formula

Abstract: Purpose Previous work using laboratory-based paradigms documented that WDRC may improve gap detection compared to linear amplification. The purpose of this study was to measure temporal resolution using WDRC fit with compression ratios set for each listener’s hearing loss. Method Nineteen adults with mild-to-moderate hearing loss fitted with WDRC or linear amplification set to a prescriptive fitting method participated in this study. Subjects detected amplitude modulations and gaps. Two noise carriers were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…Since fast-acting DRC reduces the depth of modulation in the temporal envelope, this type of processing might be able to restore the normal internal representation of the envelope in LSNHL. Brennan et al (2013) obtained MDTs with noise carriers in conditions with and without DRC for LSNHL and found higher MDTs in the conditions with DRC, consistent with the idea that DRC may compensate for recruitment. However, the study did not consider to what extent the DRC processing restored performance to the level found for listeners with NH.…”
Section: Introductionsupporting
confidence: 78%
“…Since fast-acting DRC reduces the depth of modulation in the temporal envelope, this type of processing might be able to restore the normal internal representation of the envelope in LSNHL. Brennan et al (2013) obtained MDTs with noise carriers in conditions with and without DRC for LSNHL and found higher MDTs in the conditions with DRC, consistent with the idea that DRC may compensate for recruitment. However, the study did not consider to what extent the DRC processing restored performance to the level found for listeners with NH.…”
Section: Introductionsupporting
confidence: 78%
“…Glasberg and Moore (1992) and noted that gap detection thresholds better approximated those for listeners with NH when the listeners with SNHL listened via fast (15 ms attack time, 30 ms release time) instead of slow (300 ms attack time, 3 s release time) compression. Brennan et al (2013) found reduced detectability of amplitude modulation with fast than slow compression for listeners with SNHL. The latter finding may appear to refute the argument that fast compression best restores measures of temporal resolution.…”
Section: Discussionmentioning
confidence: 83%
“…For example, fast-acting compression (release times <200 ms) results in a compressor output with reduced modulation depth, and therefore in reduced sensitivity to the information-bearing modulations in the speech signal (e.g., Brennan, Souza, Gallun & Stecker, 2013; Greenberg & Ainsworth, 2004). Fast-acting compression may also increase similarity between the envelope modulations of the signal and the envelope modulations of a masking noise (e.g., Stone & Moore, 2008).…”
mentioning
confidence: 99%